SET domain containing 7 promotes oxygen-glucose deprivation/reoxygenation-induced PC12 cell inflammation and oxidative stress by regulating Keap1/Nrf2/ARE and NF-κB pathways. Issue 3 (1st March 2022) - Pan, Xianfang; Fan, Jin; Peng, Fang; Xiao, Li; Yang, Zhiyi
ABSTRACT: Oxidative stress and inflammation are implicated in the pathogenesis of cerebral ischemia-reperfusion (I/R) injury. SETD7 (SET Domain Containing 7) functions as a histone lysine methyltransferase, participates in cardiac lineage commitment, and silence of SETD7 exerts anti-inflammatory or antioxidant capacities. The effect of SETD7 in in vitro cell model of cerebral I/R injury was investigated in this study. Firstly, adrenal pheochromocytoma cell (PC12) was conducted with oxygen-glucose deprivation/reoxygenation (OGD/R) to establish cell model of cerebral I/R injury. OGD/R-enhanced SETD7 expression in PC12 cells. Cell viability of OGD/R-induced PC12 was reduced, while the apoptosis was promoted. Secondly, knockdown of SETD7 reversed the effect of OGD/R on cell viability and apoptosis of PC12. Moreover, OGD/R-induced inflammation in PC12 with decreased interleukin (IL)-10, increased IL-6, IL-1β, tumor necrosis factor-α (TNF-α), and cyclooxygenase 2 (COX-2) were restored by knockdown of SETD7. Thirdly, knockdown of SETD7 attenuated OGD/R-induced decrease of superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), and catalase (CAT), as well as increase of malondialdehyde (MDA) and reactive oxygen species (ROS) in PC12. Lastly, OGD/R-induced decrease of NF-κB inhibitor α (IκBα), increase of phosphorylated (p)-p65, p-IκBα, and Keap1 (Kelch-like ECH-associated protein 1) were reversed by silence of SETD7. Silence of SETD7 increased heme oxygenase-1 (HO-1) and nuclear factor erythroid 2-related factor 2 (Nrf2) expression in OGD/R-induced PC12. In conclusion, suppression of SETD7 ameliorated OGD/R-induced inflammation and oxidative stress in PC12 cell through inactivation of NF-κB and activation of Keap1/Nrf2/ARE pathway. Graphical abstract: uf0001